PREVALENCE OF NUTRITIONAL ANAEMIAS BASED ON SOME HEMATOLOGIC INDICES IN THE VILLAGES OF MOBARAKEH REGION OF ISFAHAN - B. Nikpour; M. Semsar Yazdi (Tehran University of Medical Sciences, 1979)
In 1979, a Community Health Survey for the purpose of establishing population babe. Services were conducted in the villages of region of ISFAHAN with a population of about 10,000. The target group involved males and females with in the age group of more than one year old. The population under study, 617 males and 565 females who were selected by household random sampling, where examined for the level of hemoglobin and percentage of hematocrit in their blood stream. The mean hemoglobin score was 14.29 gr/100 ml. for males, with a standard deviation of 1.83. For females the mean hemoglobin score was 13.29, with a standard deviation of 1.55. Also the mean score of hematocrit was 41.49 for males and 39.67 for females with standard deviation scores of 5.86 and 5.45 respectively. The "sex" factor was related to both parameters, i.e. the level of hemoglobin and percentage of hematocrit in the blood stream. A statistically significant difference between the two means was shown by test. According to WHO's (1968) definiti9n anemia, exists when level of hemoglobin in adult males and non-pregnant female and children age 6-14 is lower than 13gr/100 ml. and 12/100 ml. and 12/100 ml, respectively. Based upon this standard, 10.16% of adult males (47 cases) and 12.5% of adult non-pregnant females (73 cases) and 11.85% of children 5-14 age group (37 cases) were considered anemic in this study.